Analisis Nilai Sosial Dalam Kumpulan Cerpen Surat Untuk Bapak Karya Nidhom Khoeron - Hendriansyah Restu Omanda; Harjito Harjito; Latif Anshori Kurniawan (Universitas Maritim AMNI Semarang, 2024)
The aim of this research is to describe and determine the social values ​​contained in the short story collection Surat untuk Bapak by Nidhom Khoeron. This research uses two approaches, namely a qualitative descriptive approach and literary sociology. The data collection technique used in this research is listening and taking notes. The data analysis technique used in this research is qualitative. This research data presentation technique uses informal techniques. The results of the research show that there is social value in the short story collection Surat untuk Bapak by Nidhom Khoeron. There are three types of social values, namely compassion, responsibility and harmony of life. The first is the form of the Social Value of Love which includes Devotion, Help, Caring, Kinship and Loyalty. The two forms of Social Responsibility Values ​​include the values ​​of a sense of belonging, Discipline and Empathy. The three forms of social values ​​are harmony of life which include justice, tolerance and cooperation, democracy.